Proyecto habitacional y productivo para la recuperación de la dignidad cultural de la comunidad indígena Emberá en Bogotá (2021)
The following is a document where an architectural project of productive housing for the full I develop the life of the families of this community, thus improving not only their form of employment but also contributing to the community of the El Tintal neighborhood where this project will be implemented. As an integral part of the proposal, theories and concepts associated with the architectural reinterpretation based on the culture of this community are taken into account, to bring these elements and land them in the urban context in which it is located; At the same time, the analysis of the family dynamics of the community is carried out so as not to go against its traditions, and avoid the cultural loss that has been occurring thanks to displacement and segregation.